Microstructure and damping properties of LPSO phase dominant Mg-Ni-Y and Mg-Zn-Ni-Y alloys - Ruopeng Lu; Kai Jiao; Nanting Li; Hua Hou; Jingfeng Wang; Yuhong Zhao (Journal of Magnesium and Alloys, 2024)
This work studied the microstructure, mechanical properties and damping properties of Mg95.34Ni2Y2.66 and Mg95.34Zn1Ni1Y2.66 alloys systematically. The difference in the evolution of the long-period stacked ordered (LPSO) phase in the two alloys during heat treatment was the focus. The morphology of the as-cast Mg95.34Ni2Y2.66 presented a disordered network. After heat treatment at 773 K for 2 hours, the eutectic phase was integrated into the matrix, and the LPSO phase maintained the 18R structure. As Zn partially replaced Ni, the crystal grains became rounded in the cast alloy, and lamellar LPSO phases and more solid solution atoms were contained in the matrix after heat treatment of the Mg95.34Zn1Ni1Y2.66 alloy. Both Zn and the heat treatment had a significant effect on damping. Obvious dislocation internal friction peaks and grain boundary internal friction peaks were found after temperature-dependent damping of the Mg95.34Ni2Y2.66 and Mg95.34Zn1Ni1Y2.66 alloys. After heat treatment, the dislocation peak was significantly increased, especially in the alloy Mg95.34Ni2Y2.66. The annealed Mg95.34Ni2Y2.66 alloy with a rod-shaped LPSO phase exhibited a good damping performance of 0.14 at ε=10−3, which was due to the difference between the second phase and solid solution atom content. These factors also affected the dynamic modulus of the alloy. The results of this study will help in further development of high-damping magnesium alloys.